Photocatalytic enantioselective Minisci reaction of β-carbolines and application to natural product synthesis. Issue 2 (30th November 2022) - Luo, Mu-Peng; Gu, Yi-Jie; Wang, Shou-Guo
Abstract : A highly efficient enantioselective direct C–H functionalization of β-carbolines via a Minisci-type radical process under a photo-redox and chiral phosphoric acid cooperative catalytic system has been disclosed. Abstract : A highly efficient enantioselective direct C–H functionalization of β-carbolines via a Minisci-type radical process under a photo-redox and chiral phosphoric acid cooperative catalytic system has been disclosed. Through this protocol, a wide range of C1 aminoalkylated β-carbolines were constructed directly with high levels of enantioselectivities from readily available β-carbolines and alanine-derived redox-active esters. This transformation allows straightforward access to highly valuable enantioenriched β-carbolines, which are an intriguing structural motif in valuable natural products and synthetic bio-active compounds. This protocol has been utilized as a highly efficient synthetic strategy for the concise asymmetric total synthesis of marine alkaloids eudistomin X, (+)-eudistomidin B and (+)-eudistomidin I.